Principles of distributed database systems - Özsu, M. Tamer; Valduriez, Patrick (Upper Saddle River, NJ : Prentice Hall ; Prentice-Hall International (UK), 1999)
This book contains: Review of Computer Networks; Distributed DBMS Architecture, Database Design; Semantic Data Control; Query Processing; Transaction Management...
Keywords: Computer; Distributed databases; Distributed databases